La Motricidad Fina en el desarrollo de la preescritura en los niños de primero de básica de la Escuela de Educación Básica Benjamín Franklin, de la ciudad de Riobamba, Periodo 2021 - Chacha Lemache, Dana Vanessa (2022)
city, with the main objective being to strengthen fine motor skills in the development of pre-writing in first-year children. The research was based on investigative references, into account the information collected from reliable bibliographic documents such as: books, articles, repositories of national and international universities, etc. with a level of descriptive research, the methodology that was used was of mixed approach. non- experimental, where the analysis and collection of qualitative and quantitative data was involved, likewise, it has a non-experimental design since there was no manipulation of variables, this being a documentary investigation. In addition, observation was applied as a technique and an observation sheet as an instrument based on the general objective raised, where 10 indicators were used, with 3 scales that were used to relate the variables investigated, therefore, we worked with 3 first-year children. basic, obtaining as a result that fine motor skills are essential for the development of good prewriting, being part of this process with exercises, activities and educational games that stimulate visual-motor skills and coordination. This will be reflected in the mastery and precision of fine movements and will give them autonomy and security in academic performance and daily activities, thus achieving the development of their independence and the performance of increasingly complex activities.